The role of digital diplomacy in the foreign policy of countries (Latakia University Journal - Economic and Legal Sciences Series, 2025)
Digital diplomacy is a modern topic in the international and diplomatic arena, which emerged as a result of technical and technological progress, and the information and communications revolution, as digital diplomacy relies on technical and technological means to interact on the international arena.The research addresses the role of digital diplomacy in the foreign policy of countries, by studying the nature of diplomacy at the level of concepts that emerged after technical and technological progress, studying the nature of digital diplomacy and its tools, and addressing the experiences of some countries in the field of digital diplomacy.The research relies on the descriptive analytical approach, and the descriptive approach is based on describing and analyzing the nature of digital diplomacy. The research reached results and recommendations, the most important of which are: The state's strength is estimated not only in relying on traditional forms of power from natural resources and military capabilities, but the technical and technological aspect has become a form of state power, establishing special training centers in the field of digital diplomacy and interest in artificial intelligence technologies.
Keywords: Diplomacy, digital diplomacy, foreign policy, cyberspace